2006
DOI: 10.1001/jama.295.21.2516
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib in Patients With Metastatic Renal Cell Carcinoma

Abstract: clinicaltrials.gov Identifier: NCT00077974.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
663
5
28

Year Published

2006
2006
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,138 publications
(732 citation statements)
references
References 23 publications
(29 reference statements)
25
663
5
28
Order By: Relevance
“…34,35 Sunitinib targets selectively VEGF, KIT, FLT3, RET, PDGFRA, and PDGFRB 36,37 and the fact that CSF1R shares structural and organizational homology with those receptor tyrosine kinases suggests a relevant role of CSF1R as a target of sunitinib in renal cell carcinoma patients. Furthermore, recent studies using hematopoietic colony assays demonstrated that imatinib targets CSF1R at therapeutic concentrations, 38,39 further indicating that CSF1R may represent a future valuable therapeutic target of receptor tyrosine kinase drug inhibitors in renal cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Sunitinib targets selectively VEGF, KIT, FLT3, RET, PDGFRA, and PDGFRB 36,37 and the fact that CSF1R shares structural and organizational homology with those receptor tyrosine kinases suggests a relevant role of CSF1R as a target of sunitinib in renal cell carcinoma patients. Furthermore, recent studies using hematopoietic colony assays demonstrated that imatinib targets CSF1R at therapeutic concentrations, 38,39 further indicating that CSF1R may represent a future valuable therapeutic target of receptor tyrosine kinase drug inhibitors in renal cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19] The utility of these agents including Sunitinib and Sorafenib in a neoadjuvant setting has yet to be explored. Patients at higher risk of developing metastatic disease may be counseled about the potential for metastases and the potential need for adjuvant therapy after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their treatment may be more difficult, and it is possible that combination with other antitumor approaches might be useful. For renal cell cancer, antiangiogenic approaches are appealing due to universal von Hippel Lindau pathway defects, which result in high expression of vascular endothelial growth factor and subsequent strong angiogenic signaling, as corroborated in recent human trials (45,46). Despite obvious efficacy, complete responses have been rare, a survival benefit has not yet been shown, and few or no patients are cured.…”
Section: Discussionmentioning
confidence: 99%